Status and Perspectives of Biomass Use for Industrial Process Heat for Industrialized Countries. Issue 8 (12th June 2020) - Lenz, Volker; Szarka, Nora; Jordan, Matthias; Thrän, Daniela
Abstract: Full reduction of greenhouse gas emissions involves transforming the industrial process heat supply. The status and future perspectives of biomass for industrial heat mainly based on the German example are reviewed, and a more differentiated consideration by a newly introduced method is attempted. The article focuses on temperature levels above 200 °C combined with an individual examination of most energy‐consuming industrial subsectors according to the feasibility of biomass utilization. Numerous studies conclude that biomass use will shift substantially from residential to industrial heat. Results indicate that biomass could play a bigger role especially for cement and clinker production, but they indicate also a significant need for further research and development to take final conclusions. Abstract : Decarbonization of the energy system includes the transformation of heat supply for industry. The easiest way seems to be an increasing usage of bioenergy. But, a review about the status of today's utilization of biomass for process heat and future perspectives based on the German example shows a significant lack of information on the most interesting processes to employ limited biomass resources.